Experimental investigation of the quasi-static axial crushing behavior of filament-wound CFRP and aluminum/CFRP hybrid tubes. (15th June 2018) - Sun, Guangyong; Wang, Zhen; Hong, Jiaying; Song, Kai; Li, Qing
Abstract: This study aims to investigate the effects of winding angles (25°, 50°, 75°, 90°; the 0° winding angle is along the axial direction of the tube) and thicknesses (3-ply, 6-ply, 9-ply) on crashworthiness characteristics of carbon fiber reinforced plastics (CFRP) tube and aluminum/CFRP hybrid tube molded by the filament winding technique through quasi-static crushing tests. The interaction between the outer CFRP tube and inner aluminum tube in a hybrid configuration was explored by comparing the sum of energy absorption of individual components with the hybrid form. It was found that both winding angle and wall thickness had significant influence on failure modes and crushing characteristics of both CFRP and hybrid tubes. With the same laminate thickness, increasing the winding angle decreased the specific energy absorption ( SEA ), energy absorption ( EA ) and peak crushing force ( PCF ) of pure CFRP and hybrid tubes. With the same winding angle of CFRP tube, increasing the thickness of CFRP tube increased the SEA, EA and PCF of both the CFRP and hybrid tubes. The SEA of 9-ply CFRP tube with winding angle of 25° and 9-ply CFRP/aluminum hybrid tube with winding angle of 25° were the highest of all the CFRP and hybrid tubes (48.74 J/g and 79.05 J/g), respectively. Moreover, EA of the hybrid tube exceeded the sum of that of the individual components thanks to the positive interaction between these components; making the hybrid tubes better crashworthiness than individual components.